Oral trauma in Brazilian patients aged 0-3 years - Cunha, Robson Frederico [UNESP]; Pugliesi, DMC; Vieira, AED (Munksgaard Int Publ Ltd, 2001)
The aim of the present investigation was to gather data pertaining to dental trauma in 1654 patients aged 0-3 years, attended at the Baby Clinic of the School of Dentistry at Aracatuba - UNESP, Brazil. The prevalence of traumatic injuries was 16.3%. There was greater involvement of boys (62.6%), of children aged 1-2 years (39.9%) and of the maxillary central incisors (86%). Falls were more often the etiology for dental injuries (58.3%). There was a predominance of uncomplicated crown fractures (48.4%).
Keywords: dental injuries; trauma; primary teeth; crown fractures; luxation injuries